2020
DOI: 10.1038/s41598-020-69120-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of the INSR gene as a mediator of the association between prenatal exposure to famine and adulthood waist circumference

Abstract: The aims of this study were to explore whether DNA methylation at INSR and IGF2 mediated the association of prenatal exposure to the Chinese great famine with adulthood waist circumference (WC) and BMI. A total of 235 subjects were selected into the present study from severely affected province and a neighbor province with less severely affected famine in China through multi-stage clustered random sampling. DNA methylation at the INSR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…More recently, Tobi et al demonstrated that DNA methylation mediated the association between prenatal famine exposure with adult BMI and triglycerides [62]. Similar observations of maternal famine exposure on changes in DNA methylation in the offspring were also reported in other studies [63][64][65][66].…”
Section: Nutrition and Dna Methylationsupporting
confidence: 66%
“…More recently, Tobi et al demonstrated that DNA methylation mediated the association between prenatal famine exposure with adult BMI and triglycerides [62]. Similar observations of maternal famine exposure on changes in DNA methylation in the offspring were also reported in other studies [63][64][65][66].…”
Section: Nutrition and Dna Methylationsupporting
confidence: 66%
“…Genome-wide screening has revealed differential methylation of expression pathways regulating growth and metabolism in particular in those exposed to the famine during early gestation [25][26][27]. Similar epigenetic relationships have also been found in adults exposed to the Chinese famine [28,29].…”
Section: Human Peri-conception Undernutrition and Offspring Healthmentioning
confidence: 60%
“…In people prenatally exposed to this famine, increased methylation level of INSR gene involved in growth and metabolism has been found in late adulthood [ 39 ]. More recently, prenatal Chinese famine exposure was found to be significantly associated with higher overall methylation level of INSR gene and larger adulthood waist circumference [ 40 ]. From these and other findings, it has been suggested that early-life exposure to the Chinese famine can be an important contributor to current epidemics of T2D in China [ 27 , 41 ].…”
Section: Epigenetic Memory Of Prenatal Famine Exposurementioning
confidence: 99%